EFFECTS OF TERRORISM ON POLITICS AND ECONOMY IN KENYA - Jumanne, Andrew Shangarai; Ontiri, Stanely Motieri; Kimolo, Benjamin (American Journal of Public Policy and Administration, 2019)
Terrorist activities refers to organized use of violence aiming to send a political message with the motive of influencing disapproval voice and policy (Congleton, 2002). This has prompted political scientists and economist to give insights on terrorism and the consequences aftermath especially in their elaboration on who becomes a terrorist, causes of terrorism, optimal counterterrorism policy, government-terrorist negotiations, internal politics of terrorist organizations and terrorism and radical mobilization (De Mesquita, 2008). Kenya being the gateway to east and central Africa, a tourism destination, an investment hub, a host of United Nations Environment Programme and a technological center in the region has attracted the interest of many groups. Among the groups was the tourists and investors who were to boost Kenya's economy through foreign currency exchange and full employment of resources respectively. On the same note, the country too has attracted the terrorism activities who have occasionally disrupted the nation's fabric leading to detrimental effects on the economic growth and the political landscape. This paper seeks to generate policy recommendations to the Kenyan government based on the literature from across the globe